The world's wildfires - Rowell, Rebecca (Special reports (Essential Library (Firm)), 2021)
Draws on current events to examine the history, causes, effects, and costs of wildfires around the world. Also explores the role climate change plays in wildfires, and how firefighters battle wildfires. Includes color photographs, a glossary, and further resources.